Влияние параметров микроплазменного напыления на структуру, фазовый состав и текстуру покрытий из гидроксиапатита - Борисов, Ю.С.; Борисова, А.Л.; Туник, А.Ю.; Войнарович, С.Г.; Кислица, А.Н.; Кузьмич-Янчук, Е.К.; Карпец, М.В. (Автоматическая сварка, 2008)
Задачей данной работы было исследование влияния различных параметров микроплазменного напыления на характеристики покрытий из гидроксиапатита, а также определение эффективности влияния на свойства покрытий такого средства управления фазовым составом, как термическая обработка нанесенного покрытия. Hydroxyapatite (HA) coatings were deposited on a titanium alloy substrate by the microplasma spraying (MPS) method.
The method of factorial experiment with fractional replicas was used to study relationship between the MPS parameters (current, plasma gas flow rate, spraying distance, and powder consumption) and characteristics of the HA coatings (microstructure, morphology, content of crystalline and amorphous phases, and texture). The effect of coating thickness
and subsequent heat treatment of the deposited layer on phase composition and texture of the coatings was calculated.
The results demonstrate that the coating formation process has some special features under the MPS conditions.